2016
DOI: 10.1111/iwj.12698
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of collagen/oxidised regenerated cellulose/silver‐containing composite wound dressing for the treatment of medium‐depth split‐thickness skin graft donor site wounds in multi‐morbid patients: a prospective, non‐comparative, single‐centre study

Abstract: Split-thickness skin grafting (STSG) is a widely used method in reconstructive surgery, but donor site wounds (DSWs) are often slow healing and painful. This prospective study evaluated the performance of a composite wound dressing containing collagen/oxidised regenerated cellulose in the treatment of medium-depth (0·4 mm) DSWs in 25 multi-morbid patients with chronic leg ulcers requiring STSG. The range of patients' ages was 44-84 years (mean 71·6 years) with DSW sizes ranging between 12 and 162 cm (mean 78 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 55 publications
1
14
0
1
Order By: Relevance
“…75 According to current data, moderate wound colonization (EWMA stage 2 and 3) has minor influence on wound healing compared to reduced microcirculation and malnutrition. 9,76,77 All four MRSA patients in our study showed rapid wound healing after SVF application. The patient with multiresistant E. coli colonization had a large, predominantly ischaemic AVLU as well as ankle arthrodesis and showed slight progression of the wound size, but no signs of progressive infection after treatment.…”
Section: Discussionmentioning
confidence: 61%
“…75 According to current data, moderate wound colonization (EWMA stage 2 and 3) has minor influence on wound healing compared to reduced microcirculation and malnutrition. 9,76,77 All four MRSA patients in our study showed rapid wound healing after SVF application. The patient with multiresistant E. coli colonization had a large, predominantly ischaemic AVLU as well as ankle arthrodesis and showed slight progression of the wound size, but no signs of progressive infection after treatment.…”
Section: Discussionmentioning
confidence: 61%
“… 42 The use of ORC/collagen dressings has also been examined in 25 skin graft donor sites in patients with multiple comorbidities and chronic leg ulcers. 43 Complete re-epithelialization was observed between 10 and 34 days postoperatively in all wounds. Two patients developed signs of infection after the first dressing change; however, antibiotics were not needed.…”
Section: Literature Search Resultsmentioning
confidence: 82%
“…Two patients developed signs of infection after the first dressing change; however, antibiotics were not needed. 43 An article by Mees et al 44 describes a treatment pathway in 62 patients with postoperative infected abdominal wounds. These wounds were first treated antiseptically and then with antimicrobial advanced wound dressings until the wound improved to stage 1, followed by ORC/collagen/silver-ORC dressings in combination with alginate dressings.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudo realizado por Ulrich et al 95 onde foi analisada ação de ORC/colágeno no exsudato de feridas diabéticas concluiu que ORC/colágeno apresentou a propriedade de diminuir os níveis de MMPs (MMP-2) do exsudato havendo melhor evolução das feridas, corroborando com outras publicações. Também foi testada a capacidade de proliferação desses fibroblastos expostos a três diferentes concentrações de ORC/colágeno (1.4, 2.8 e 4.2 mg/mL) sendo observada maior proliferação nas concentrações 2.8 e 4.2 mg/mL.Assim, os estudos apresentados sugerem que a ORC/colágeno possui a propriedade de estimular a proliferação de fibroblastos, diminuir a concentração de MMPs no microambiente da ferida, proteger fatores de crescimento21,87,94,95 e ainda quando associada à prata agregar característica de diminuir a proliferação de microrganismos e evitar infecção23,96 .Contudo, apesar dos estudos previamente citados, ainda há lacunas quanto a interferência da ORC/colágeno, associada ou não à prata, no componente celular presente no leito de úlceras crônica, assim, em nosso estudo pretendemos verificar a ação in vitro dessas substâncias em fibroblastos oriundos de úlcera venosa, buscando elucidar efeitos desse curativo nos processos celulares e consequentemente no microambiente da ferida. Todas as feridas apresentavam tecido de granulação em moderada quantidade, pouco ou nenhum tecido necrótico e ausência de sinais clínicos de infecção e não estavam sendo tratadas com curativo contendo prata na sua composição.…”
unclassified